Characteristics of dendritic cells from patients with rheumatoid arthritis and different type of drug therapy - Yu. D. Kurochkina; M. A. Tikhonova; T. V. Tyrinova; O. Yu. Leplina; A. E. Sizikov; A. E. Sulutian; L. P. Konenkova; O. A. Chumasova; A. A. Ostanin; E. R. Chernykh (Бюллетень сибирской медицины, 2018)
Purpose of the study. Comparative study of the phenotypic and functional properties of dendritic cells (DC) in groups of patients with rheumatoid arthritis (RA) receiving disease-modifying drugs, or biological drugs and (or) pulse therapy with high doses of glucocorticoids.Materials and methods. The study included 39 patients with RA and 20 age-appropriate and semihealthy donors. Nineteen patients were treated with standard disease-modifying drugs (BMP) in the form of monotherapy or in combination (group PA1) at the time of the examination, 20 – biological preparations or pulse-therapy with glucocorticoids (group PA2). In the latter case, the examination was carried out for 2–7 days after the last injection of methylprednisolone.Results. In this study, the properties of DC generated from monocytes under the action of IFN-α (IFN-DK) for RA are described for the first time. It has been established that the general feature of DC in the PA1 and PA2 groups are signs of immaturity of the DC, manifested by increased CD14 expression and a decrease in the proportion of mature (CD14-CD83 +) DC. Despite the differences in DC in the PA1 and PA2 groups, both cell types retain in vitro sensitivity to dexamethasone, the treatment of which leads to a significant inhibition of TNF-α production and a decrease in allostimulant activity of the DC. Thus, IFN-DK in RA patients receiving medical therapy is characterized by the presence of tolerogenic properties, which are most pronounced when used in a program of treatment of biological agents or pulse therapy with corticosteroids.